Strategi Reformasi Birokrasi Di Tingkat Lokal: Perspektif Good Governance Dalam Otonomi Daerah Kecamatan Kwandang - Ibrahim, Risky; Olii, Rara Ayudyah (UNIVED PRESS, Universitas Dehasen Bengkulu, 2024)
This study aims to analyze bureaucratic reform strategies at the local level using the perspective of good governance in the framework of regional autonomy, a case study in Kwandang District, North Gorontalo Regency. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. The results of the study show that although bureaucratic reform efforts have been carried out through simplification of procedures, digitization of services, and capacity building of apparatus, their implementation still faces obstacles in the form of limited resources, weak public participation, and the principles of transparency and accountability have not been optimal. The findings of the study also reveal the gap between policy design and practice on the ground, as well as the need for more contextual and participatory strategies. As a novelty, this study identifies the potential for a collaborative approach based on local wisdom in strengthening the implementation of good governance at the sub-district level. Therefore, continuous efforts are needed to strengthen a bureaucratic culture that is responsive, accountable, and public service-oriented. This research makes a theoretical and practical contribution to the development of a more adaptive bureaucratic reform strategy in the era of regional autonomy.